Pengaruh Return on Investment (ROI), Earning Per Share (EPS), Net Profit Margin (NPM), dan Market Value Added (MVA) Terhadap Return Saham - Desmy Riani; N.A Rumiasih; Hannisa Rahmaniar Hasnin; Muhamad Ridwan (Journal on Education, 2023)
e capital market has a fairly strong role in increasing economic stability in a country, because the capital market is used as a means of business funding and as a means for the public to invest. This study aims to determine the partial and simultaneous effect of Return on Investment (ROI), Earning Per Share (EPS), Net Profit Margin (NPM), and Market Value Added (MVA) on Stock Returns in Banking Companies listed on the Indonesia Stock Exchange. (IDX). This type of research uses a quantitative approach. The population in this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period, namely 44 companies. Sampling using purposive sampling method, and obtained a sample of 12 companies. Data collection techniques were carried out by means of documentation studies and literature studies. The data analysis technique used in this study is descriptive statistical analysis, classical assumption test, and multiple linear regression analysis techniques. The results of the study show: partially Return on Investment (ROI) and Market Value Added (MVA) have a positive and significant effect on Stock Returns, Earning Per Share (EPS) has no effect on Stock Returns, and Net Profit Margin (NPM) has a negative and significant to Stock Return. Meanwhile, simultaneously Return on Investment (ROI), Earning Per Share (EPS), Net Profit Margin (NPM), and Market Value Added (MVA) have no effect on Stock Returns.